Evidence-Based Practice: An Alternative to Authority-Based Practice (Revisiting Our Heritage). Issue 3 (July 2018) - Gambrill, Eileen
Editor's note: This article is reprinted from Volume 80-4 (1999) as part of the Revisiting Our Heritage series. Nearly 20 years ago, one of the earliest articles to appear in a social work journal on evidence-based practice (EBP) was presented by Eileen Gambrill. While many are familiar with Gambrill's contributions as a pioneer of the EBP movement in social work, it is worth noting her emphasis on client voice as a vital part of EBP in advancing the field's efficacy: "Evidence-based practice requires an atmosphere in which critical appraisal of practice-related claims flourishes, and clients are involved as informed participants. A notable feature of EBP is attention to clients' values and expectations. Clients are involved as active participants in the decision-making processes." As you reflect on two decades of EBP influence in research, practice, and policy, consider how successful (or not) social work has progressed in keeping the foundation of client self-determinism strong and relevant.